Qualificação e imputação de dados sobre satisfação de hipertensos cadastrados na estratégia saúde da família - Moreira, Raquel de Negreiros (2012)
The quality of information has been of particular interest in health. It is known that the incompleteness of information is a very common problem in information systems and epidemiological studies. Thus, it has been imputation as a solution of the missing data, which are created artificially complete set of data subject to statistical analysis. This study aimed to analyze the data quality HIPERDIA items on satisfaction and hypertensive patients of the Family Health Strategy in the city of João Pessoa / PB on the service and the use of imputation methods for missing data. Secondary data were obtained from duplicate HIPERDIA, the hypertensive patients enrolled between 2006/2007 in 36 family health teams, resulting in a representative sample of 343 users in the city of João Pessoa / PB. As a primary source was constructed an instrument consisting of eight core dimensions of primary care, measured on Likert scale ranging from "0" to "5". The techniques were applied to the method of Single Imputation: Replacement for Central Value Trend (TC), Hot Deck, Estimated Maximum Likelihood (MV) and Multinomial Logistic Regression (RLM), were compared using the percentage of correct answers, average error square (RMSE) and mean absolute percentage error (MAPE). Was built to simulate two different scenarios sample with different proportions of missing data (5%, 10%, 15%, 30% and 40%). The comparison of the allocation methods, for variable setting with a type having overlapping response to the other, the method was that TC gave better performance, followed by the method of RLM. For the scenario with homogeneous frequency response, the best method was to RLM. The study has demonstrated that there are still errors in the completion of HIPERDIA and that allowed us to recover the imputation characteristics of the representation of the original data, verifying that the imputation methods adopted brought reliability and reduction of bias in the sample proportions of up to 40% of missing data.